BUILDING NATION CHARACTER THROUGH TAHFIZ PROGRAM IN SMP IT AL ANIS KARTASURA - Muhammad Arif Wicagsono; Syamsul Hidayat (Universitas Muhammadiyah Surakarta, 2019)
Character education is an effort to fortify and improve the noble and fundamental values of life so as to build a person with a distinctive or special character. It also seeks to build harmonious relationships between a person with family and society in undergoing the role of character education on a collective basis. Furthermore, a range of methods is employed to conduct such an education, including through the program of Qur’an memorization or known as tahfiz. This study aims to find the relevance of the program in fostering the noble character of the nation. It used a qualitative descriptive approach, with observation and in-depth interviews as data collection methods. The data analysis technique was the inter-method comparative analysis, which was applied in memorizing the Qur’an. This study was conducted at SMP Al-Anis Kartasura, Central Java, Indonesia. The study found there are various methods for memorizing the Qur’an, such as Yanbu’a, Tikrar, Muri-Q, and Qira’ati. The characters instilled in the program include religious, disciplined, trustworthy, curios, bibliophilic, responsible, creative, appreciative, and friendly/communicative.